Effects of stocking density on feather pecking and aggressive behavior in Thai crossbred chickens - Huo, Xin; Na-Lampang, Pongchan (Agriculture and Natural Resources, 2016)
The influence of stocking density on feather pecking and aggressive behavior of Thai crossbred chickens was investigated from age 4e12 wk. In total, 900 day-old mixed sex Thai crossbred chickens were assigned to three replicates of 100 birds per pen, at stocking densities of 8 birds/m2, 12 birds/m2 and 16 birds/m2, respectively. The frequency of feather pecking, the number of pecks per bout, pecking intensity and the frequency of aggressive behavior were recorded once a week by scanning all the birds in the pen. It was found that the stocking density had no effect on the frequencies of feather pecking on body areas except on the wings area (p < 0.05). The stocking density had no effect on the occurrence of 1-4 pecks per bout or 5-9 pecks per bout. The stocking density had no significant influence on the pecking, pinching or plucking intensity, except on the intensity of pulling. The different types of aggressive behavior such as stand-off, fight, threat, leap, chase, avoidance and peck were not affected by the stocking density. In conclusion, stocking density did not affect the feather pecking activities and aggressive behavior of Thai crossbred chickens. However, further work is suggested with a larger number of replications to establish that there is no effect of stocking density, as the power of this study was low.